Prevalence, Demographic, and Clinical Correlates of Comorbid Depressive Symptoms in Chinese Psychiatric Patients With Alcohol Dependence - Huang, Hui; Zhu, Zhigan; Chen, Hongxian; Ning, Kui; Zhang, Ruiling; Sun, Wei; Li, Bing; Jiang, Haifeng; Wang, Wenzheng; Du, Jiang; Zhao, Min; Yi, Zhihua; et al. (Frontiers in Psychiatry, 2020)
Background: Depressive symptoms are common among psychiatric patients with alcohol dependence (AD). However, the prevalence and clinical correlates of comorbid depressive symptoms are less well studied in Chinese Han patients. Methods: In this hospital-based survey, we recruited 378 psychiatric patients diagnosed with AD according to the Diagnostic and Statistical Manual of Mental Disorders-Fourth Edition (DSM-IV). All patients completed the Beck Depression Inventory (BDI) to evaluate depressive symptoms and the Alcohol Use Disorders Identification Test (AUDIT) to assess the severity of drinking. Results: Compared to patients without depressive symptoms, 48.9% (185/378) of the patients with comorbid depressive symptoms were younger, had a more unstable marital status, had a higher AUDIT total score, and had a higher adverse consequences subscore (all P<0.05). Further logistic regression analysis showed that unstable marital status (Odds ratios [OR] =2.20, 95% confidence interval [CI] 1.21-3.99) and AUDIT total score (OR=1.07, 95% CI 1.03-1.11) were significantly associated with depressive symptoms. Conclusions: Our findings indicate high comorbidity between AD and depressive symptoms in Chinese psychiatric patients. Moreover, some variables are correlates of comorbid depressive symptoms. Particular attention should be paid to the early detection and intervention for this comorbid condition and its risk factors.